2019
DOI: 10.3390/molecules24183260
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Salicylate Glycosides in Some Italian Varietal Wines

Abstract: Glycosides are ubiquitous plant secondary metabolites consisting of a non-sugar component called an aglycone, attached to one or more sugars. One of the most interesting aglycones in grapes and wine is methyl salicylate (MeSA), an organic ester naturally produced by many plants, particularly wintergreens. To date, nine different MeSA glycosides from plants have been reported, mainly spread over the genera Gaultheria, Camellia, Polygala, Filipendula, and Passiflora. From a sensorial point of view, MeSA has a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Occurrence of relatively high levels of free and glycosidically-bound methyl salicylate were also observed, in agreement with recent observations concerning this compound’s high content and its glycosidic precursors in Trebbiano di Soave and Verdicchio wines [ 28 , 29 , 49 ]. Methyl salicylate is characterized by a distinctive mint, wintergreen aroma [ 50 ], and could further contribute to the balsamic character of these wines.…”
Section: Resultssupporting
confidence: 89%
“…Occurrence of relatively high levels of free and glycosidically-bound methyl salicylate were also observed, in agreement with recent observations concerning this compound’s high content and its glycosidic precursors in Trebbiano di Soave and Verdicchio wines [ 28 , 29 , 49 ]. Methyl salicylate is characterized by a distinctive mint, wintergreen aroma [ 50 ], and could further contribute to the balsamic character of these wines.…”
Section: Resultssupporting
confidence: 89%
“…Other important benzenoids: methyl salicylate is an organic ester naturally produced by many plants, particularly wintergreens, and also present in wine, sometimes in quite high quantities, such as in the Verdicchio and Lugana varieties [38,39]. It was demonstrated that it could be present in both free and bound form (MeSA glycosides).…”
Section: Gewürztraminer Winementioning
confidence: 99%
“…Recently, the aromatic complexity of Verdicchio wines was described, also relating to its aging. Younger wines were characterized by fruity and tropical notes, while aged wines were distinguished by the presence of norisoprenoids, anise and balsamic notes, related to 3-methyl-2,4-nonanedione and methyl salicylate released by precursors [6]. The presence of varietal thiols, namely 3-mercaptohexan-1-ol and its acetate form, conferring tropical and citrus notes has been documented in Trebbiano di Lugana wine.…”
Section: Introductionmentioning
confidence: 99%